A phase I dose-escalation and dose-expansion study of brontictuzumab in subjects with selected solid tumors - Ferrarotto, R.; Eckhardt, G.; Patnaik, A.; LoRusso, P.; Faoro, L.; Heymach, J.V.; Kapoun, A.M.; Xu, L.; Munster, P. (Annals of oncology, 2018)
Brontictuzumab is a monoclonal antibody that targets Notch1 and inhibits pathway activation. The purpose of this first-in-human study was to determine the maximum tolerated dose (MTD), safety, pharmacokinetics, immunogenicity and preliminary efficacy of brontictuzumab in patients with solid tumors. Subjects with selected refractory solid tumors were eligible. Brontictuzumab was administered intravenously at various dose levels and schedule during dose escalation, and at 1.5mg/kg every 3 weeks (Q3W) during expansion. Evidence of Notch1 pathway activation as determined by an immunohistochemistry assay was required for entry in the expansion cohort. Adverse events were graded according to the NCI-CTCAE v 4.03. Efficacy was assessed by RECIST 1.1. Forty-eight subjects enrolled (33 in dose escalation and 15 in the expansion phase). The MTD was 1.5mg/kg Q3W. Dose-limiting toxicities were grade 3 diarrhea in two subjects and grade 3 fatigue in one subject. The most common drug-related adverse events of any grade were diarrhea (71%), fatigue (44%), nausea (40%), vomiting (21%), and AST increase (21%). Brontictuzumab exhibited nonlinear pharmacokinetics with dose-dependent terminal half-life ranging 1–4days. Clinical benefit was seen in 6 of 36 (17%) assessable subjects: 2 had unconfirmed partial response (PR) and 4 subjects had prolonged (≥6months) disease stabilization (SD). Both PRs and three prolonged SD occurred in adenoid cystic carcinoma (ACC) subjects with evidence of Notch1 pathway activation. Pharmacodynamic effects of brontictuzumab were seen in patients’ blood and tumor. Brontictuzumab was well tolerated at the MTD. The main toxicity was diarrhea, an on-target effect of Notch1 inhibition. An efficacy signal was noted in subjects with ACC and Notch1 pathway activation. NCT01778439